Strategic Impact (D.C.A.A.T.A) In Mental Alertness Among Fourth Year Middle School Students In Chemistry - Hassan, Ahmed Hanawi; Al-Anabi, Dr. Wafa Abd Al- Razzaq Abbas (South Eastern European Journal of Public Health, 2024)
The eresearch aim.s too iidentify the impact of the strategyy [(D.C.A.A.T.A) in mental alertness among fourth-year middle school students in chemistry].The quasi-experimentall design wass adopted for thee experimentall and controll groupss withi the posttest, where the sample size was (73) students, distributed among (36) forr thee experimentall groupp andd (37) forr thee controll groupp, and too achieve Objective of the research: The researchers built a measure of mental alertness consisting of (28) items according to Langer’s four dimensions. After applying the measure too thee twoo researchh groupp, the researchers analyzed thee results. It became clear thatt thee studentss of thee experimentall groupp were superiorr too thee studentse thee controll groupp according to thee (D.C.A.A.T.A) strategy in the measure of mental alertness, and that The size of the effect of the (D.C.A.A.T.A) strategy was very large on the mental alertness scale, and in light of this, the following conclusion was reached that teaching according to the (D.C.A.A.T.A) strategy contributed to improving thee levell off mental alertness off fourthh-yearr middlee schooll studentss inn chemistry.